Investigation on the current-zero characteristic of vacuum circuit breakers. (December 2016) - Ge, Guowei; Liao, Minfu; Duan, Xiongying; Huang, Zhihui; Huang, Jinqiang; Zou, Jiyan
Abstract: The current-zero characteristic of vacuum circuit breakers (VCBs) has an important influence on the dynamic dielectric recovery and the success of the breaking test. In the paper, the characteristic of the post-arc current, post-arc charge and the post-arc conductance at current-zero is researched to obtain the influence of the arc memory on the current-zero characteristic and the post-arc characteristic. Based on the synthetic test circuit, the test plat of the current-zero characteristic is set up and the test VCB is a transparency vacuum interrupter in order to observe the development and extinguishing process of the vacuum arc by the high speed CMOS camera. The distribution law of post-arc characteristic is gained by measuring and processing the post-arc current. The relationship between the post arc charge and the final position of last cathode spot is investigated. The current-zero characteristic of VCBs supply the base for controlling vacuum arc, improving the breaking capacity, which maybe also useful to VCBs with multi-break. Highlights: The post-arc characteristic such as the post-arc current, conductance and charge is obtained by measuring and process the post-arc current. The post-arc charge is more stable and smooth, so it is more optimal to describe the post-arc characteristic. The post-arc charge can be used to describe the residual plasma at current zero and it is the effect of the arc memory. The post-arc charge increases as the arcing time increases and the influence of the current magnitude is weak when the current is from 5 kA to 15 kA. The relationship between the final position of the last cathode spot and the post-arc characteristic is gained and analyzed.